Coaxial bright and dark field optical coherence tomography - Wang, Yukun (2024)
Optical coherence tomography (OCT) has been widely used in biomedicine. However, the signal collection efficiency of the standard OCT is sub-optimal since only the direct scattered light in the bright field is used. Almost 75% of multiple scattered light in the dark field is wasted. Here, we demonstrate a novel coaxial optical design that simultaneously collects bright and dark field signals. We implemented a wavefront-division beam splitter in the sample arm with a 45-degree rod mirror, which reflects the illumination. We detected light within its circular aperture in a way similar to the standard OCT and allowed the dark-field light of the annular-shaped aperture to pass and be collected by the dark-field detection channel. The bright and dark field signals are directed to the same spectrometer via a fiber array. With this scheme, multiple scattered light can be collected; the signal collection efficiency is improved by ~3dB for typical biological tissues. We demonstrate that the dark-field OCT images provide higher resolution and more information than the standard bright-field OCT, and compounding of bright and dark field images suppresses the speckles by ~√2. We validated these advantages with Teflon phantoms, chicken breast ex vivo, and human skin in vivo. We believe that this new configuration will greatly promote the OCT technique for biomedical applications.